Pengaruh Kombinasi Pijat BBLR dan KMC (Metode Kangaroo Mother Care) terhadap Rooting Sucking Reflex di RSUD Dr RM. Djoelham Binjai - Parida Hanum; Fitri Anggraini; Mawar Wati Duha; Sri Nova Julianti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
The infant mortality rate (IMR) is an indicator of the welfare of a nation that reflects the level of public health problems. Based on the IDHS in 2007, in Indonesia the IMR reached 34/1000 and decreased in 2017 to 32/1000, and around 56% of infant deaths occurred in the neonatal period. This study aims to determine the differences in the rooting-sucking response in newborns using a combination of low birth weight massage and the Kangaroo Mother Care method with the Kangaroo Mother Care method only. This type of research is experimental. The research design is a quasi-experimental research design with pre-test and post-test control group design. This research was conducted at Dr Hospital R. M Djoelham in November 2021. The subjects of this study were 40 Low Birth Weight neonatus consisting of 20 intervention groups and 20 control groups. sampling strategy that uses total sampling, the number of samples can be as many as 40 samples. The data collection instrument was a stopwatch and an observation sheet for the rooting-sucking reflex. The data were analyzed using Mann Whiteney and Wilcoxon. There was a significant difference between the combination treatment of Low Birth Weight, massage and the Kangaroo Mother Care method method with the Kangaroo Mother Care method alone.